2019
DOI: 10.12688/f1000research.18338.2
|View full text |Cite
|
Sign up to set email alerts
|

A refinement to the formalin test in mice

Abstract: The constant refinement of tests used in animal research is crucial for the scientific community. This is particularly true for the field of pain research, where ethical standards are notably sensitive. The formalin test is widely used in pain research and some of its mechanisms resemble those underlying clinical pain in humans. Immediately upon injection, formalin triggers two waves (an early and a late phase) of strong, nociceptive behaviour, characterised by licking, biting, lifting and shaking the injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 73 publications
1
14
0
2
Order By: Relevance
“…The mice in this study were anesthetized which may also influence the timing of the behavior as the early part of the response is clearly reduced. 47 Both the automated system and Bryant 36 showed that C57BL/6N males lick less regardless of the bin choice, but bin size for females heavily influenced the outcome. Experiments using either C57BL/6N or C57BL/6NJ as control mice need to consider the sexes separately, as they show clear differences in timing over Phase II.…”
Section: Discussionmentioning
confidence: 99%
“…The mice in this study were anesthetized which may also influence the timing of the behavior as the early part of the response is clearly reduced. 47 Both the automated system and Bryant 36 showed that C57BL/6N males lick less regardless of the bin choice, but bin size for females heavily influenced the outcome. Experiments using either C57BL/6N or C57BL/6NJ as control mice need to consider the sexes separately, as they show clear differences in timing over Phase II.…”
Section: Discussionmentioning
confidence: 99%
“…Given different pruritogens may induce itch through a distinct mechanism, different acute itch models are still needed to be developed. Since first reported over 40 years ago, the formalin test has been widely used in pain research and evaluation of analgesic drugs in laboratory animals ( 50 ), and formalin test is known to capture some mechanisms that are likely to be relevant to many pain patients in clinic ( 51 ). The nociceptive responses induced by formalin are marked by licking, biting, lifting, and shaking the injected hindpaw in rodents ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that a non-covalent agonist (GNE551) had distinct binding pocket and ligand-interaction mechanism for TRPA1 ( 56 ). Unlike the covalent agonist AITC, GNE551 activated TRPA1 without desensitization and induced persistent pain ( 51 ). Thus, targeting TRPA1 may be a novel strategy for developing new anti-nociception or anti-itch compounds, which is consistent with previous reports ( 7 , 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…O teste se baseia na contagem do número de contorções abdominais, caracterizada por contração e rotação do abdômen, seguida pela extensão de uma ou ambas as patas traseiras. O número de contorções abdominais é avaliado durante 20 minutos, iniciando-se dez minutos após a administração de ácido acético (Coolier et al, 1968, Parada et al, 2001Lopes et al, 2019)…”
Section: Estudo Da Dor Em Pesquisa Básicaunclassified
“…O intervalo de quiescência entre a primeira e a segunda fase é resultado de uma inibição da transmissão nociceptiva através de circuitos supra-espinais e espinais. A resposta comportamental característica é a da lambida da pata (Lopes et al, 2019)…”
Section: Estudo Da Dor Em Pesquisa Básicaunclassified